Perception of Accounting Practitioners on MASB TRi - Abdul Aziz, Abdullah; Abdullah, Ibrahim; Mohd Rizuan, Abdul Kadir; Abdul Aziz, Abdullah (2013)
Zakat is one of the pillars of Islam and part of ibadah (obligation) for Muslims. Zakat has been identified as an important source of financial seed to jumpstart the economy of the Muslim community and give an impact to socio-economy development of a nation. Today, Zakat is no longer limited to the domain of religious or shari’ah studies and discourses, but an effort has been taken to restore back its function as a tools to strengthen Muslims economics. Many initiatives have been taken to facilitate its collection. An accounting standard relate to the Zakat payment MASB TRi-1 (Malaysian Accounting Standard, Technical Release Islamic – Number 1). Accounting for Zakat on Business, had been issued to facilitate the Zakat computation on business. The purpose of the release of MASB TRi-1 is to standardize the recognition, measurement, presentation and disclosure of zakat on business. However, MASB TRi-1 does not have the same weighted as standards. The objective of the study is to gauge the perception of accounting practitioners about MASB TRi-1. Questionnaires were sent to 282 accounting practitioners who have studied either Islamic accounting or Islamic finance. The finding revealed that most of the practitioners, regardless of their religious beliefs, are very keen to learn and deal with MASB TRi-1. Another encouraging finding is that the disclosure required by MASB TRi-1 encompasses the objective of Islamic Accounting